2017
DOI: 10.1007/s10209-017-0546-8
|View full text |Cite
|
Sign up to set email alerts
|

On the accessibility of Moodle 2 by visually impaired users, with a focus on mathematical content

Abstract: In this paper we study the accessibility by visually impaired people of the Learning Management System (LMS) Moodle 2. The study is conducted by testing four different visually impaired subjects, with different degrees of disability and performing different tasks connected to different roles in the LMS. A peculiar focus is given to the accessibility of content involving mathematics. At the end of the paper some recommendations to improve the accessibility of Moodle 2 are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…В работе [22] 2010 года есть указание на ограниченное использование плагинов доступности в версиях Moodle, развернутых на базе учебных заведений; однако в ходе текущего анализа платформы обнаружены опции расширения доступности для пользователей, включая систему принудительного добавления альтернативного текста к рисункам, инструменты проверки доступности контента в текстовых редакторах, визуальный редактор формул LaTeX, инструменты для взаимного преобразования форматов LaTeX и MathML. В работе [23] приведены данные, подтверждающие доступность редакторов LaTeX в интерфейсе Moodle для пользователей с глубокими нарушениями зрения.…”
Section: Discussionunclassified
“…В работе [22] 2010 года есть указание на ограниченное использование плагинов доступности в версиях Moodle, развернутых на базе учебных заведений; однако в ходе текущего анализа платформы обнаружены опции расширения доступности для пользователей, включая систему принудительного добавления альтернативного текста к рисункам, инструменты проверки доступности контента в текстовых редакторах, визуальный редактор формул LaTeX, инструменты для взаимного преобразования форматов LaTeX и MathML. В работе [23] приведены данные, подтверждающие доступность редакторов LaTeX в интерфейсе Moodle для пользователей с глубокими нарушениями зрения.…”
Section: Discussionunclassified
“…Med glavne lastnosti označevalnih jezikov lahko uvrščamo njihovo prilagodljivost, saj se vsebina lahko zelo hitro prilagodi za prikaz na zaslonu, za tisk ali za nadaljnjo obdelavo z morebitnimi transformacijami. Zaradi svojih prednosti se pogosto uporabljajo v akademskem in inženirskem okolju [24], v veliki meri pa lahko olajšajo delo slepim in slabovidnim uporabnikom [3].…”
Section: Strukturirano Zapisovanje Besedila In Označ Evalni Jezikiunclassified
“…Narrated the importance of using mobile learning in Higher Learning Institutions in Tanzania when shifting to blended learning and allow learners to access learning resources anywhere [3]. Examined the accessibility by visually impaired people of the Learning Management System (LMS) Moodle available by evaluating all assistive technologies available in smart devices [7]. Examine the challenge facing visually impaired learners in accessing graphical contents in Australian HLI and found that teaching style and perceptions of teachers can hinder the accessibility [8].…”
Section: Background Informationmentioning
confidence: 99%